Revisiting Generic Science Skills as 21st Century Skills on Biology Learning (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The purpose of this study was to describe the generic skills of students’ science who conducted experiments on biology learning grade VIII Junior High School (SMP) in Batusangkar. This study used a descriptive quantitative design. The variables of this research were generic science skills as the 21st-century skills and students achievement. A total of 295 students were used as the populations and the purposive sampling technique was employed to select one class as the research sample (n=32 students). The student activities, such as a direct observation, awareness of scale, logical framework, cause-effect, modeling, and the inference was observed by 6 observers. This activity was designed and adapted based on the generic science skills and 21st-century skills. The percentage of students’ achievement and generic science skills score was analyzed with descriptive statistics. The students’ achievement showed that all students were successful, with a mean score 75. The students’ generic science skills mean scores was categorized as: very good, good and sufficient, and all students were completed the learning. The highest (very good) performance was on the modeling activities with the average percentage of 87.49%. The results indicated that the skills were considered to be part of generic science skills and 21st-century skills. The results of this study concluded and suggested the need to revisit and reaffirm the inclusion of generic science skills in biology learning because this skill becomes part of or similar to the 21st-century skills.